1992
DOI: 10.1055/s-2007-1003354
|View full text |Cite
|
Sign up to set email alerts
|

Serum Procalcitonin as an Index of Inhalation Injury in Burns

Abstract: The molecular heterogeneity of serum immunoreactive calcitonin (iCT) was analyzed from a prospective study of 41 burn patients. Using different region-specific anticalcitonin antisera, the ratio of mid-region-recognizing to carboxyl terminal-region-recognizing iCT was found to increase acutely in those who subsequently died. The highest ratios occurred in those who died early of respiratory complications. Sephadex chromatography and reversed-phase HPLC demonstrated that the serum iCT circulated predominantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(51 citation statements)
references
References 11 publications
2
48
0
1
Order By: Relevance
“…140,146 Both BLPs and calcitonin have important functions in human lung pathophysiology. 13,147,148 Recent studies using baboons and genetically engineered mice have revealed a potential mechanistic link between BLPs derived from PNECs and chronic inflammatory lung disease. 13 BLPs are known to promote normal fetal lung development.…”
Section: Innervation and Chemoreception Function Of Pnecsmentioning
confidence: 99%
“…140,146 Both BLPs and calcitonin have important functions in human lung pathophysiology. 13,147,148 Recent studies using baboons and genetically engineered mice have revealed a potential mechanistic link between BLPs derived from PNECs and chronic inflammatory lung disease. 13 BLPs are known to promote normal fetal lung development.…”
Section: Innervation and Chemoreception Function Of Pnecsmentioning
confidence: 99%
“…It is a stable protein ex vivo in plasma with a half-life of 24–29 h. It can routinely be used in laboratory examination of blood samples without any coling substitutes. The first reports from Assicot et al [6] and Nylen et al [7] demonstrate that calcitonin precursor molecules are found in patients with sepsis and bacterial inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in the most severe inflammation of noninfectious aetiology, no PCT elevations could be observed, except in severe acute pancreatitis [14,15] and inhalation injuries in burns [16].…”
mentioning
confidence: 99%